Identification of known and novel immunogenic T-cell epitopes from tumor antigens recognized by peripheral blood T cells from patients responding to IL-2-based treatment - Scheibenbogen, Carmen; Song, Mingxia; Schadendorf, Dirk (International journal of cancer, 2002)
In previous studies CD8+ T cells specific for melanocyte antigens have been frequently found in melanoma patients responding to interleukin-2 (IL-2)-based therapies. In our study we analyzed the suitability of using circulating T cells from melanoma patients with clinical response after IL-2-based therapy to identify novel T-cell epitopes from defined tumor antigens. Using unstimulated peripheral blood mononuclear cells and the interferon-γ (IFN-γ) ELISPOT assay, we studied CD8+ T-cell responses against 5 peptides from the tumor antigen tyrosinase (Tyr) selected by epitope prediction using an HLA-A1-binding computer algorithm. T cells specifically secreting IFN-γ in response to 3 of these 5 peptides, namely, Tyr (454-463), Tyr (146-156) and Tyr (243-251), could be detected in 4 of 4 HLA-A1-positive patients with clinical response. In contrast, no T-cell responses against these peptides were seen in 6 HLA-A1-positive melanoma patients with progressive disease and in 8 healthy subjects. We could generate specific cytotoxic T lymphocytes (CTL) against Tyr (454-463) using peptide-pulsed autologous dendritic cells as antigen-presenting cells. The induced CTLs efficiently killed melanoma cells that express HLA-A1 and tyrosinase. The peptides Tyr (146-156) and Tyr (243-251) had recently been identified as CTL epitopes by other groups. Further ex vivo characterization of the T cells reactive against the novel epitope Tyr (454-463) in 1 patient by multicolor flow cytometry showed specific CD3+/CD8+/IFN-γ+ T cells with frequencies of up to 0.41% of the CD3+/CD8+ T-cell population. Most of this T-cell population also expressed granzyme B. Our data confirm that in patients with tumor regressions induced by immunotherapy or chemoimmunotherapy circulating T cells reactive with tyrosinase epitopes can frequently be detected. Peripheral blood T cells from such patients are a valuable source for screening peptides selected by epitope prediction This strategy facilitates the rapid identification of immunogenic T-cell epitopes that are probable targets of immune-mediated tumor rejection. © 2002 Wiley-Liss, Inc.
Gesehen am 11.11.2020